ANALISIS IMPLEMENTASI PENDIDIKAN KARAKTER PADA SISWA KELAS XII IPA2 SMAN 1 PULAU PUNJUNG - Almen Almen (Dharmas Education Journal (DE_Journal), 2020)
The background of this research is the lack of character education in the younger generation, with the number of moral crisis occurrences in daily life. This study aims to implement character education for XII IPA2 students of SMAN 1 Pulau Punjung, Dharmasraya Regency. This research method uses descriptive qualitative. The research subjects were assessed by 23 students of class XII IPA2 at SMAN 1 Pulau Punjung, Dharmasraya Regency. The data technique was carried out by means of observation, interviews, questionnaires, and documentation. The data analysis technique in the study used the Miles and Huberman model consisting of data reduction, data presentation, and data levers. The actions taken by the teacher in an effort to implement character education were by using exemplary and habituation methods. The results showed that the questionnaire responses of class XII IPA2 students of SMAN 1 Pulau Punjung for the "very high" category were 14 students with a proportion of 61%, for the "high" category were 9 students with a proportion of 39%, for the low and very low category was the proportion. 0%.